(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This article provides a comprehensive analysis of the constitutional guarantees established to safeguard and promote the rights of youth in the Republic of Uzbekistan. It elucidates the progressive provisions introduced in the 2023 Constitution concerning youth development, as well as the legislative and institutional mechanisms embedded in the Law “On State Youth Policy” and relevant presidential decrees. Furthermore, the study explores the modernization of the national education system, the enhancement of youth participation in socio-political life, and the consolidation of legal frameworks ensuring their social protection and professional growth. Particular attention is devoted to the implementation of the “New Uzbekistan – 2030” strategy, which embodies the nation’s long-term vision for sustainable development, civic engagement, and the creation of equitable opportunities for the younger